Mengungkap Strategi dan Mekanisme Koping Caregiver Keluarga Pasien Skizofrenia: Literature Review - Ni Putu Cyanda Cahya Dewi; Made Diah Lestari (Universitas Kristen Maranatha, 2024)
Schizophrenia is a severe mental disorder. The impact of this disorder not only affects patients, but also their families who are caregivers. An unstable family psychological condition can make it difficult for families to cope and make appropriate and wise decisions in meeting patient needs. The family's ability to make the right decisions depends on effective coping strategies and mechanisms that are adjusted to the situation and problems experienced by each caregiver family during the treatment period. Therefore, the researcher aims to provide an overview of the appropriate coping strategies and mechanisms used by schizophrenia caregiver families that are adjusted to their conditions. The method used in this study is a literature review through a search on three databases, Google Scholar, Researchgate, and Crossref, so that eleven articles were analyzed. The results of this study show differences in the coping process carried out by schizophrenia caregivers as an adaptation response to the conditions experienced including emotional focused coping strategies, problem focused coping strategies, adaptive coping mechanisms, maladaptive coping mechanisms, and religious coping. The use of these coping strategies and mechanisms is adjusted again according to their respective effectiveness according to the condition of the caregiver when caring for schizophrenia patients.